A forebrain undivided: Unleashing model organisms to solve the mysteries of holoprosencephaly. Issue 8 (1st May 2019) - Grinblat, Yevgenya; Lipinski, Robert J.
Abstract: Evolutionary conservation and experimental tractability have made animal model systems invaluable tools in our quest to understand human embryogenesis, both normal and abnormal. Standard genetic approaches, particularly useful in understanding monogenic diseases, are no longer sufficient as research attention shifts toward multifactorial outcomes. Here, we examine this progression through the lens of holoprosencephaly (HPE), a common human malformation involving incomplete forebrain division, and a classic example of an etiologically complex outcome. We relate the basic underpinning of HPE pathogenesis to critical cell‐cell interactions and signaling molecules discovered through embryological and genetic approaches in multiple model organisms, and discuss the role of the mouse model in functional examination of HPE‐linked genes. We then outline the most critical remaining gaps to understanding human HPE, including the conundrum of incomplete penetrance/expressivity and the role of gene‐environment interactions. To tackle these challenges, we outline a strategy that leverages new and emerging technologies in multiple model systems to solve the puzzle of HPE. Key Findings: Incomplete division of the forebrain primordium results in holoprosencephaly (HPE), a common human malformation with a complex, poorly understood etiology. Key cell and molecular interactions that drive early forebrain development are conserved across vertebrates. Standard genetic approaches are not sufficient to address the major gaps in our understanding of HPE pathogenesis, namely, the role of gene‐environment interactions and the reasons for incomplete penetrance and expressivity of HPE‐linked genes. Powerful new and emerging technolog ies available in model organisms will be necessary to address these remaining knowledge gaps.